The Effectiveness of Al-Khawarizmi Module Based on Numbers Among Gifted and Talented Muslim Students - Norazlina Subani; Akif Zafran Normanhisham; Farith Akhtar Rahmat; Akil Naeem Muslim (Kolej PERMATA Insan, 2024)
4th Insan Junior Researchers International Conference 2023 (iJURECON 2023) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Nurhidaya Mohamad Jan, Nur Aisyah Mohamed, Nur Fatin Fathillah Mazlan 27-28 October 2023